2007
DOI: 10.1007/s10162-007-0085-8
|View full text |Cite
|
Sign up to set email alerts
|

Spectral-Ripple Resolution Correlates with Speech Reception in Noise in Cochlear Implant Users

Abstract: Speech perception ability in noise is one of the most practical measures of success with a cochlear implant; however, with experience, this ability can change dramatically over time, making it a less than ideal tool for comparing performance among different processing strategies. This study examined performance on a spectral discrimination task and compared it to speech perception in noise. An adaptive procedure was used to determine the spectral-ripple density that subjects could discriminate. A closed-set, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
324
6
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 241 publications
(366 citation statements)
references
References 25 publications
34
324
6
2
Order By: Relevance
“…Stimuli with a ripple density of 1.414 ripples/octave and a ripple depth of 30 dB were used for this analysis. This ripple density was chosen because it was similar to the average spectral-ripple discrimination thresholds for the no-dead region condition in the current study as well as to the average performance reported for 31 CI subjects by an earlier report (Won et al 2007). The top panels show the electrode outputs for the redistributed conditions, whereas the bottom panels show the electrode outputs for the dropped conditions.…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…Stimuli with a ripple density of 1.414 ripples/octave and a ripple depth of 30 dB were used for this analysis. This ripple density was chosen because it was similar to the average spectral-ripple discrimination thresholds for the no-dead region condition in the current study as well as to the average performance reported for 31 CI subjects by an earlier report (Won et al 2007). The top panels show the electrode outputs for the redistributed conditions, whereas the bottom panels show the electrode outputs for the dropped conditions.…”
Section: Discussionmentioning
confidence: 79%
“…When there was no dead region, CI subjects showed an average threshold of 1.80 ripples/octave, which is similar to an earlier report using the same spectralripple test. Using 31 CI subjects, Won et al (2007) reported an average threshold of 1.73 ripples/octave. When NH subjects were tested with a 16-channel vocoder with no-dead region, they showed worse performance than CI subjects.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…From the signal processing stand point, it is generally accepted that two main factors contribute to reduced speech identification in noise for CI users: (1) limited spectral resolution including the negative effect of channel interaction (e.g., Fu et al 1998;Friesen et al 2001;Fu and Nogaki 2005;Won et al 2007; Verschuur 2009), and (2) inability to deliver FM information through current CI speech processors (e.g., Smith et al 2002;Qin and Oxenham 2003;Stickney et al 2005;Zeng et al 2005;Gnansia et al 2010). The latter point should be stated more precisely because speech FM information can be transmitted in the form of recovered AM cues through the CI speech processor and CI users are able to exploit the recovered AM cues for speech identification (Won et al 2012).…”
Section: Discussionmentioning
confidence: 99%